Women on board of Malaysian public listed companies - Fadzil, Faudziah Hanim (American Scientific Publishers, 2015)
The Prime Minister Datuk Seri Najib Tun Razak has recognised the importance of women’s contribution of the country’s development in 2011 through the cabinet approved the policy of having at least 30% women as decision makers in corporate sector.In addition, at the launch of the 9th World Islamic Economic Forum (WIFE) 2013 in London, the Prime Minister mentioned that Malaysia has given empowerment to the women to involve in entrepreneurship.Therefore, this paper descriptively provides details of Malaysian women in public listed companies.This study analyses the recent trends of the women labour force participation for 2002, 2009 and 2011.These findings provide useful information for government, private sectors and especially women to know the current situation of women participation as decision makers in corporate sector, thus, increase the role of Malaysian women in the corporate sector.